New Approach for the On-Line Spectrophotometric Determination of Vanadium (V) In Different River Water via the Use of a Homemade Ayah 6SX1-T-2D Solar-Continuous Flow Injection Analyser - Al-Awadie, Nagam S.Turkey; A. Yassin, Omar (Iraqi Journal of Science, 2025)
A new simple sensitive and selective spectrophotometric method has been developed for the analysis of vanadium(V) in three randomly chosen samples from river water at different locations by continuous flow injection analysis. The method based on the oxidation of pyrogallol by vanadium(V) in acidic solution to form color species and the same species was determined using homemade Ayah 6SX1-T-2D solar cell analyser . Chemical and physical parameters were investigated using the high intensity of snow white light emitted diode as a source. The linear dynamic range for the instrument response versus vanadium(V) concentration was 1-200 mg.L-1 with correlation coefficient r = 0.9920. The limit of detection (S/N=3) was 70 ng/ sample from the step wise dilution for the minimum concentration in the linear dynamic range of the calibration graph with RSD % of lower than 1% at 90 mg.L-1 (n=5) concentration of vanadium(V). The method was applied successfully for the determination of vanadium (V) in three river samples. A comparison was made between: both of the proposed methods and classical method (UV-Vis spectrophotometry at wave length 427 nm) using the standard additions method via the use of paired t-test. It was noticed that there was no significant difference between two methods at 95 % confidence level.